Developing an Islamic Farayez system applying software engineering - Tabassum, Sadia; Hoque, A. H. M. Sajedul; Twahura, Sharaban; Rahman, Mohammad Osiur (Penerbit Universiti Kebangsaan Malaysia, 2019)
Distribution of deceased person’s wealth is a divine law in Islam. This distribution should be accurate; otherwise a gruesome punishment is waiting in hereafter. The combination of relatives of late person is diverse which makes the computation of distribution difficult. In order to ease the computation of shares of slain person, a software system can be designed for Islamic Farayez which is the premier concern of this article. The existing software systems cannot compute the distribution precisely always and furthermore have lack of proper explanation of the system. Having studied ‘Islamic Shariah’ for all possible combinations of relatives of dead person, a system has been modelled and developed which provides the knowledge of Islamic inheritance and distributes the wealth of deceased accurately through which user can be galvanized to follow. Here the Islamic Farayez has been analyzed and modelled using structured approach. After fixing different scenario of Islamic Farayez of a dead person, individual cases are analysed using three levels of Data Flow Diagram (DFD). Hence, DFD illustrated the organization of the functional components of the system; and as a consequence, based on this, the graphical form of algorithm or flow-chart of the overall Islamic Farayez system is developed. Finally, mathematical models are derived for all possible combination of relatives of late person and then developed the software for Islamic Farayez system. The reliability, accuracy, integrity and robustness of the proposed Islamic Farayez system are rigorously justified by comparing the proposed system generated results with manual results as well as other existing software generated results for various complex cases. It is recommended to use this proposed Islamic Farayez system as an expert assistant for distribution of deceased person’s wealth among his/her eligible relatives.